Growth performance, organ weight, and plasma metabolites in broiler chickens fed corn-soybean meal diet containing berry pomaces and fed without or with multienzymes supplement - Munene Kithama; Youssef I. Hassan; Xianhua Yin; Kelly Ross; Carl Julien; Yan-Martel Kennes; Elijah G. Kiarie; Moussa S. Diarra (Poultry Science, 2023)
ABSTRACT: This study evaluated effects of feeding low-bush wild blueberry (LBP) and organic American cranberry (CRP) pomaces without or with multienzyme supplement (ENZ) on growth performance, organ weight and plasma metabolites in broiler chickens. Nonenzyme-fed (no-ENZ: n = 1,575) and enzyme-fed (ENZ: n = 1,575) day-old male Cobb500 broilers were placed in floor pens (45 chicks/pen) and allocated to five corn-soybean meal-based diets: a basal diet supplemented with either bacitracin methylene disalicylate (BMD, 55 mg/kg), 0.5 or 1% of CRP or LBP in a 2 × 5 factorial design for 35-day experiment. Body weight (BW), feed intake (FI) and mortality were recorded whereas BW gain (BWG) and feed conversion ratio (FCR) were calculated. Birds were sampled at days 21 and 35 for organ weights and plasma metabolites. There were no interactions between diet and ENZ on any parameter (P > 0.05) and no effect of ENZ on overall (d 0–35) growth performance and organ weights (P > 0.05). Birds fed BMD were heavier (P < 0.05) at d 35 and had better overall FCR than berry-supplemented birds. Birds fed 1% LBP had poor FCR than birds fed 0.5% CRP. Birds fed LBP exhibited heavier liver (P < 0.05) than birds fed BMD or 1% CRP. The highest plasma concentrations of aspartate transaminase (AST), creatine kinase (CK) at d 28 and gamma-glutamyl transferase (GGT) at d 35 were found in ENZ-fed birds (P < 0.05). At d 28, birds fed 0.5% LBP showed higher plasma AST and CK concentrations (P < 0.05). However, CRP feeding resulted in a lower plasma CK level compared with BMD feeding (P < 0.05). The lowest cholesterol level was detected in 1% CRP-fed birds. In conclusion, this study showed no ENZ effects to potentiate berry pomaces on the overall growth performance of broilers (P < 0.05. However, plasma profiles revealed the potential of ENZ to modulate the metabolism of pomace-fed broilers. LBP increased BW during the starter phase, while CRP increased BW during the grower phase.